Drought resistance of tobacco overexpressing the AfNAC1 gene of Amorpha fruticosa Linn. - Li, Minghui; Liu, Ziang; Liu, Chenxi; Zhu, Fengjin; Wang, Kai; Wang, Zhenyu; Li, XiuFeng; Lan, Xingguo; Guan, Qingjie (Frontiers in Plant Science, 2022)
Plants are often adversely affected by abiotic stresses such as drought, low temperature, and salinity during growth, and plant NAC-like transcription factors are involved in regulating growth and developmental processes in response to stresses such as drought and salinity. In this study, to investigate the function of AfNAC1, a co-expression network of AfNAC1 genes was constructed using gene expression data from the Chinese legume deciduous shrub, Amorpha fruticosa Linn... A 576 bp NAC transcription factor (AfNAC1 gene, MN180266) encoding 191 amino acids was isolated from Amorpha fruticosa seedlings by RT-PCR. qRT-PCR showed that the AfNAC1 gene was expressed in roots, stems, leaves, and flowers of Amorpha fruticosa. However, drought stress significantly increased root expression, and AfNAC1 protein was localized in the nucleus by green fluorescence detection. In this study, the drought resistance of overexpressing tobacco was analyzed in depth. Under natural drought stress, the chlorophyll and antioxidant enzyme activities of overexpressing plants were significantly higher than those of wild-type (WT) plants, but the MDA content was lower than that of WT; after rehydration, the Fv/Fm values of AfNAC1-overexpressing tobacco recovered faster than those of wild-type tobacco and rapidly reached the control levels; AfNAC1 may be involved in the regulation of the photosystem and indirectly in the regulation of the plant in response to drought stress.